Getting to yes : negotiating agreement without giving in - Fisher, Roger (Penguin Books New YorkUS, 1991)
Provides step-by-step strategy for resolving conflicts at all levels. Addresses issues including: the meaning and limits of principled negotiation; how to deal with persons who seem to be irrational or have different value systems; and, the role of power in negotiations. Includes answers to ten frequently-asked questions about negotiation.